2001
DOI: 10.1001/archinte.161.16.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia After Cardiac Arrest Is Associated With an Unfavorable Neurologic Outcome

Abstract: Hyperthermia is a potential factor for an unfavorable functional neurologic recovery after successful cardiopulmonary resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
218
0
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(235 citation statements)
references
References 27 publications
6
218
0
11
Order By: Relevance
“…Only half of the febrile episodes are attributable to infection, with nosocomial pulmonary infections representing the largest contributor [19]. Observational and retrospective studies have demonstrated that fever is associated with poor neurological outcome in the first 72 h after cardiac arrest [20,21], stroke [22], intracerebral hemorrhage [23], subarachnoid hemorrhage [24], and traumatic brain injury [25][26][27]. In spinal cord injuries, animal studies have revealed that induced hyperthermia immediately after the injury is associated with increased tissue damage and worse outcomes compared to normothermic conditions [28].…”
Section: Detrimental Effects Of Fevermentioning
confidence: 99%
“…Only half of the febrile episodes are attributable to infection, with nosocomial pulmonary infections representing the largest contributor [19]. Observational and retrospective studies have demonstrated that fever is associated with poor neurological outcome in the first 72 h after cardiac arrest [20,21], stroke [22], intracerebral hemorrhage [23], subarachnoid hemorrhage [24], and traumatic brain injury [25][26][27]. In spinal cord injuries, animal studies have revealed that induced hyperthermia immediately after the injury is associated with increased tissue damage and worse outcomes compared to normothermic conditions [28].…”
Section: Detrimental Effects Of Fevermentioning
confidence: 99%
“…The message from this study is not that we should abandon temperature control; patients in both arms of the trial had their temperature controlled and, most importantly, fever, which is associated with poor neurological outcome after cardiac arrest [18], was prevented. Even after return to normothermia after a period of TH, continued temperature control is important.…”
mentioning
confidence: 99%
“…4,5,[7][8][9] Some benefits of hypothermia may result from avoidance of hyperthermia as temperatures over 37°C are common in post-arrest patients and are associated with increased risk of unfavourable neurologic recovery. 7 In fact, in post-arrest patients each degree Celsius over 37 is associated with increased risk of severe disability, coma, or persistent vegetative state. 7 These data are the basis for the recommendation to avoid hyperthermia 10 (temperatures over 38°C; Grade B), and to institute treatment to avoid temperatures over 37°C (Grade D).…”
mentioning
confidence: 99%
“…7 In fact, in post-arrest patients each degree Celsius over 37 is associated with increased risk of severe disability, coma, or persistent vegetative state. 7 These data are the basis for the recommendation to avoid hyperthermia 10 (temperatures over 38°C; Grade B), and to institute treatment to avoid temperatures over 37°C (Grade D). Gradual rewarming was practiced in the post-arrest hypothermia randomized controlled trials, 4,5 and is supported by data from hypothermic head injured patients 11 (Grade B).…”
mentioning
confidence: 99%